FAKTOR KONSENTRASI DAN KONDISI TUNAK RADIOAKTIF PERUNUT 109Cd PADA KERANG HIJAU (PERNA VIRIDIS) - Yusni Ikhwan Siregar (Program Pascasarjana Universitas Riau, 2007)
Laboratory study on the concentration factors and steady state condition of Cadmium (Cd) by green mussel (Perna viridis) has been carried out. Radiotracer 109Cd was applied in the study. The objective of the study was to evaluate bioaccumulation parameters including con- cent ration factors and steady state condition of cadmium by green mussel from dissolved phase. It was found that both salinity and temperature had significant effect (P<0.001) on accumulation rate of 109Cd. The highest concentration factor of Cd (31,23-54,09) was appeared in water salinity of 29% and of water temperature 31°C. Apparently, green mussel accumulated 72,21-107,80 Bq/gr Cd at the steady state condilion. It revealed that the small Perna viridis (5.2 cm in length) accumulated 109Cd about 107,80 Bq/gr, whereas the bigger size of the green mussel (6.6 cm in length) had an uptake of about 72,21 Bq/gr.